2014
DOI: 10.1021/ja510028c
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Allosteric Interactions in Cell Signaling

Abstract: Linking cell signaling events to the fundamental physicochemical basis of the conformational behavior of single molecules and ultimately to cellular function is a key challenge facing the life sciences. Here we outline the emerging principles of allosteric interactions in cell signaling, with emphasis on the following points. (1) Allosteric efficacy is not a function of the chemical composition of the allosteric pocket but reflects the extent of the population shift between the inactive and active states. That… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
115
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 131 publications
3
115
0
Order By: Relevance
“…In PRS, we introduce perturbations by applying a random external unit force on single residues as a first-order approximation to the forces exerted on a protein in a crowded cell environment, then we analyze the residue response fluctuation profile of the rest of the chain using linear response theory. It has been shown that PRS using an elastic network model or coupled with MD can be useful to 1) obtain conformational changes upon binding (22,41); 2) identify critical residues that mediate long-range communication through dynamic allostery (10,65,(68)(69)(70); 3) predict a better binding affinity score through rapidly generating an ensemble of configurations for flexible docking (71)(72)(73); and 4) distinguish diseaseassociated and putatively neutral population variations in human proteome (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…In PRS, we introduce perturbations by applying a random external unit force on single residues as a first-order approximation to the forces exerted on a protein in a crowded cell environment, then we analyze the residue response fluctuation profile of the rest of the chain using linear response theory. It has been shown that PRS using an elastic network model or coupled with MD can be useful to 1) obtain conformational changes upon binding (22,41); 2) identify critical residues that mediate long-range communication through dynamic allostery (10,65,(68)(69)(70); 3) predict a better binding affinity score through rapidly generating an ensemble of configurations for flexible docking (71)(72)(73); and 4) distinguish diseaseassociated and putatively neutral population variations in human proteome (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…These scaffolds not only bring proteins together; the shifting landscape that they orchestrate preorganizes the ensembles for subsequent binding and catalytic events (26). The signal that these elicit propagates across the network (27). Cells acquired strategies to block cellular functions such as inflammation by targeting proteins, PPIs, and Ub chains.…”
Section: Resultsmentioning
confidence: 99%
“…Signaling pathways are also characterized by distinct activation and termination phases that govern the duration, intensity, and amplification of the signal as it is propagated through the cell (1). Signaling proteins are intrinsically dynamic and populate multiple conformational states in equilibrium and its ligands/partner proteins alter these conformational equilibria (2)(3)(4). Indeed, an overlay of protein dynamics is fundamental for bridging structure and function of signaling proteins and consequently for a molecular understanding of signal transduction (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%